Suicidal risk and locus of control in men in early maturity - Truhan, Elena A.; Sharanda, Mikhail A. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The study is aimed at finding anti-suicidal factors and correlates of reducing suicidal risk in men. The results of the correlation analysis of indicators of suicidal risk and locus of control in men during early maturity are presented. In men during early maturity suicidal tendencies decrease, but general internality increases. Between internality in various spheres and forms of suicidal intentions, mainly negative correlations were found. The pronounced anti-suicidal effect in men is possible with an increase in the general internality (especially their internality in the sphere of occupational relations).
Keywords: suicidal risk; anti-suicidal factors; locus of control; internality; early maturity